2016
DOI: 10.15407/fz62.05.083
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiarities of Arginase Pathway of L-Arginine in Spermatozoa in Men With Different Forms of Pathospermia

Abstract: При різних формах патоспермії у чоловіків досліджували зміни активності аргінази сперматозоїдів та гормональний профіль периферичної крові. Встановлено, що активність аргінази в сперматозоїдах чоловіків з олігозоо-, астенозоо-, олігоастенозоо-та лейкоцитоспермією знижується в 2,1, 2,3, 2,4 і 3,3 раза відповідно. Це вказує на пригнічення аргіназного шляху метаболізму L-аргініну, яке суттєво не залежать від типу порушення сперматогенезу. Проте зниження активності аргінази має найбільш виражений характер у пацієн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…In our previous study, we found morphological and functional semen changes in spermatozoa at excretory toxic form of men infertility that correlated with increasing LPO and decreasing of activity of glutathione antioxidant enzymes [7,18,25]. These results prompted further characterization biochemical features of glutathione antioxidant protection system in ejaculated spermatozoa of infertile men with different forms of pathospermia.…”
Section: Resultsmentioning
confidence: 81%
“…In our previous study, we found morphological and functional semen changes in spermatozoa at excretory toxic form of men infertility that correlated with increasing LPO and decreasing of activity of glutathione antioxidant enzymes [7,18,25]. These results prompted further characterization biochemical features of glutathione antioxidant protection system in ejaculated spermatozoa of infertile men with different forms of pathospermia.…”
Section: Resultsmentioning
confidence: 81%
“…РЕЗУЛЬТАТИ й ОбГОВОРЕННЯ. У наших попередніх дослідженнях дано морфологічну характеристику сперматозоїдів і встановлено накопичення продуктів пероксидації ліпідів (ПОЛ), зокрема малонового діальдегіду, в спер-матозоїдах чоловіків з екскреторно-токсичною формою неплідності, що свідчить про активацію вільнорадикального окиснення [12][13][14].…”
unclassified